The Level Of Satisfaction By Participants Program Social Security Services Agency For Health Services Maternal And Child - Novitasari , Ika; Sutrisno, Joko; Tsalatsatul Mufida, Riza (Journal of Global Research in Public Health, 2019)
Satisfaction patient is positive the evaluation of the dimensions of services or.Services can be evaluated a small portion of service.It was subjective, is difficult to measure, can berubah-ubah, and a lot of factor influential dimension in a total of human life. Methods used in this research is used the etnometodologi. And techniques of data collection in the sampling method of purposive technique was used in the study. A population that used in research it is a whole join the bpjs ( a body of the social security coverage) that his first facilities are Puskesmas Ciptomulyo Malang city. This research result indicates that the existence of of satisfaction with the service provided by paramedics who is in Puskesmas Ciptomulyo Malang city of respondents (patients) and triangulation of (community figure). Although there were several respondents (patients) feel not satisfied with the services provided they received for medical treatment, because the services from the officer who is unfriendly (judes), waiting time which is too long, space examination which is quite narrow, the officers did not quick response, lack of seating chairs when patients full of, and the limited parking lot. Based on the research that has been carried out , from the five of factors affect a patient begins to satisfaction of: (1) conformity between hope and the fact, (2) services during the process of enjoy services, (3) behavior personnel, (4) the atmosphere and the physical condition of the environment, and (5) promotion or advertisements are in accordance with the fact, and the most dominant influence satisfaction patient is factor the conformity of hope by the fact patients acquire during which the patient services at a public health center Ciptomulyo Malang city.